EDUCATIONAL MANAGEMENT AND CURRICULUM DEVELOPMENT: HOW DEVELOPED COUNTRIES DIFFER FROM DEVELOPING COUNTRIES - Haydarova Kamola Bahodir qizi (European Journal of Interdisciplinary Research and Development, 2024)
Educational management and curriculum development are key components of a successful educational system. However, there are significant differences between how these processes are handled in developed and developing countries. This article provides a comparative analysis of educational management practices and curriculum development strategies in both contexts. The study explores how factors such as government policy, resources, teacher training, and technology impact these areas. By examining case studies from both developed and developing countries, the article identifies the challenges faced by developing countries and discusses potential strategies for bridging the gap. The article concludes with recommendations for improving curriculum development and educational management in developing countries to promote equitable and quality education.